2017
DOI: 10.1016/j.athoracsur.2016.08.066
|View full text |Cite
|
Sign up to set email alerts
|

A Modified and Less Invasive Procedure in Aortic Arch Replacement

Abstract: Circulation arrest is widely used during total aortic arch replacement. However, the conventional procedures have high morbidity and mortality. We modified the hybrid procedure by optimizing the sequence of anastomosis between the graft and aorta. As a result, the time of extracorporeal circulation was obviously shortened, and cardiac arrest was needed only during the two anastomoses of the aorta with aorta graft main body. In addition, both circulation arrest and deep hypothermia were avoided. Leakage was als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Besides, the incidence of these dysfunction is positively correlated with the duration of DHCA [13][14][15][16]. Hybrid surgery can reduce the difficulty of the operation and recent complications by avoiding DHCA, but it also leads to a relatively high incidence of late complications [17,18], due to its lack of one important step of Sun's procedure that the expandable stent graft can be firmly fixed to the distal 4-branched prosthetic graft using the suture line. One study reported that the incidence of late complications was up to 48%, including delayed type I endoleak, stent migration, stent fracture and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the incidence of these dysfunction is positively correlated with the duration of DHCA [13][14][15][16]. Hybrid surgery can reduce the difficulty of the operation and recent complications by avoiding DHCA, but it also leads to a relatively high incidence of late complications [17,18], due to its lack of one important step of Sun's procedure that the expandable stent graft can be firmly fixed to the distal 4-branched prosthetic graft using the suture line. One study reported that the incidence of late complications was up to 48%, including delayed type I endoleak, stent migration, stent fracture and so on.…”
Section: Discussionmentioning
confidence: 99%
“…If the left common carotid artery is occluded by a torn intima, the first anastomosis can be performed between the left subclavian artery and graft branch [ 3 ].…”
Section: Commentsmentioning
confidence: 99%